Assessing combinatorial effects of HIV infection and former cocaine dependence on cognitive control processes: A functional neuroimaging study of response inhibition. (1st February 2022) - Wakim, Kathryn-Mary; Freedman, Edward G.; Tivarus, Madalina E.; Heinecke, Armin; Foxe, John J.
Abstract: Individuals with a diagnosis of co-morbid HIV infection and cocaine use disorder are at higher risk of poor health outcomes. Active cocaine users, both with and without HIV infection, show clear deficits in response inhibition and other measures of executive function that are instrumental in maintaining drug abstinence, factors that may complicate treatment. Neuroimaging and behavioral evidence indicate normalization of executive control processes in former cocaine users as a function of the duration of drug abstinence, but it is unknown to what extent co-morbid diagnosis of HIV affects this process. To this end, we investigate the combinatorial effects of HIV and cocaine dependence on the neural substrates of cognitive control in cocaine-abstinent individuals with a history of cocaine dependence. Blood-oxygen level dependent signal changes were measured as 86 participants performed a Go/NoGo response inhibition task while undergoing functional magnetic resonance imaging (fMRI). Four groups of participants were selected based on HIV and cocaine-dependence status. Participants affected by both conditions demonstrated the lowest response accuracy of all participant groups. In a region of interest analysis, hyperactivation in the left putamen and midline-cingulate hyperactivation was observed in individuals with both HIV and cocaine dependence relative to individuals with only one condition. Results of a whole-brain analysis indicate response inhibition-related hyperactivation in the bilateral supplementary motor area, bilateral hippocampi, bilateral primary somatosensory areas, right dorsal anterior cingulate, and left insula in the CD+/HIV+ group relative to all other groups. These results indicate complex and interactive alterations in neural activation during response inhibition and highlight the importance of examining the neurocognitive effects of co-morbid conditions. Highlights: Drug abuse is a common comorbidity of HIV infection. Effects of HIV on neural function were assessed using fMRI in former cocaine users. Participants with both conditions showed poorest response inhibition performance. Interactive effects of HIV and drug abuse observed in the cingulate and left putamen. Whole-brain analysis revealed 18 additional regions showing interactive effects.